Sponge spicule flux in Antarctic water column studied by sediment trap. - Bertolino M.; Ferranti M. P.; Cutroneo L.; Forero A.; Bavestrello G.; Capello M. (country:AUS, 2013)
In Antarctic ecosystems, siliceous sponges play a pivotal role at different levels. They are one of the main components of the benthic biota showing species diversity and biomass levels comparable with those of tropical habitats. Demosponges and hexactinellids play a crucial role in the benthic-pelagic coupling absorbing large amounts of dissolved silica that is accumulated in the opaline spicules of their skeleton.When sponges decay, the biogenic silica stored in their skeletons sunk in the sediments where, under the action of the currents, it accumulates in thick mats representing secondary biogenic substrata for benthic organisms. These free spicules show a negligible rate of dissolution representing therefore a net depletion of the dissolved silica from the system.The fluxes of biogenic silica in Antarctic waters have been mainly studied with particular regard to diatom frustules while no quantitative data are available for sponge spicules.In this paper we present the daily fluxes of sponge spicules in a sediment trap placed on a mooring 461 m depth on a bottom of 514 m depth in Terra Nova Bay (Ross Sea) from February 2003 to February 2005. The trend of the spicule sink, ranging from 7 to 19000 spicules m-2 d-1, is strongly correlated with that of total sediments with maximum values during the austral summer and minimum during winter. Spicule fluxes are significantly different among the years: the annual maximal values are always recorded in February with values of 5000, 19000 and 8000 spicules m-2 d-1, respectively for 2003, 2004 and 2005. The spicule weight, obtained from the biovolume, indicates that these structures represents 1-2% of the total sediments. From a quantitative point of view, demosponges and hexactinellids contribute with a similar amount to the total spicule number. Also the entire spicules and the fragments are almost evenly represented in the trap, suggesting an equivalent supply from living sponges and from sediment resuspension